Answer:
The value of y is
.
Step-by-step explanation:
Consider the provided equation.
![aby-b=c](https://tex.z-dn.net/?f=aby-b%3Dc)
It is given that a, b, and c are constants and y is the variable.
We need to solve the equation for y.
First add b to the both side.
![aby-b+b=c+b](https://tex.z-dn.net/?f=aby-b%2Bb%3Dc%2Bb)
![aby=c+b](https://tex.z-dn.net/?f=aby%3Dc%2Bb)
Now isolate the variable.
Divide both sides by ab.
![\frac{aby}{ab}=\frac{c+b}{ab}](https://tex.z-dn.net/?f=%5Cfrac%7Baby%7D%7Bab%7D%3D%5Cfrac%7Bc%2Bb%7D%7Bab%7D)
![y=\frac{c+b}{ab}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7Bc%2Bb%7D%7Bab%7D)
Hence, the value of y is
.